Validation and Reliability Testing of the Yonsei Lifestyle Profile for Assessing Multifaceted Health Lifestyles - Young‐Myoung Lim; Ah‐Ram Kim; Seung‐Ju Lim; Ji‐Hyuk Park (Health Care Science)
ABSTRACT Background In this study, we aimed to validate and test the reliability of the Yonsei lifestyle profile (YLP) in assessing multifaceted health lifestyle levels in a study population from the United States. Methods The YLP‐English version and health‐promoting lifestyle profile II were administered to 100 individuals living in the United States. Concurrent validity was analyzed using Pearson's correlation coefficient, and discriminant validity was examined by comparing sex and age differences through t‐tests and multiple variance analysis. Internal consistency was assessed using Cronbach's α for each sub‐factor. Results The YLP‐English Version demonstrated concurrent validity with the Health‐Promoting Lifestyle Profile II, showing consistent correlations for the total score (0.3, p < 0.01) and frequency sub‐factors (0.25–0.69, p < 0.01). Among the satisfaction sub‐factors, only nutrition showed a weak negative correlation (−0.19, p < 0.01); all others were nonsignificant. Discriminant validity revealed no significant sex differences, but physical activity frequency varied across age groups. Internal consistency was high (Cronbach's α = 0.80–0.86). Conclusion In this study, we validated the YLP‐English version as a reliable instrument for assessing health‐related lifestyle behaviors. The YLP uniquely captures both lifestyle frequency and satisfaction, offering a comprehensive perspective on health behaviors. Although this tool is currently most applicable in population‐level studies, future research should establish clinical thresholds to enhance its utility in individualized health assessments and interventions.